Social, Economic and cultural dimension of sporting spectacle - Ławniczak, Paweł (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
Sports event is this aspect of sport, which is experienced by most people. Sports games, competitions, matches shape the image of the sport in the popular consciousness.The article includes analysis of the sporting spectacle – the essential aspects and function. The analysis aimed to identify possible prospects of viewing sport as a social phenomenon. As a result of the analysis, nine possible prospects were identified as possible discussion on the sports spectacle. Sports competitions, matches can be viewed from the following perspectives symbolic, emotional, recreation and health, economic, social and political, architectural as well as in the perspective of art and media.